Symbolism and Identity in the Burning Stone Tradition: A Comparative Study Between Mountain and Coastal Communities of Manokwari, Papua - Donald Kasenda (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The tradition of stone burning is a cultural ritual that has a deep meaning and has long been attached to the community in Papua. This study compares the symbolism and intention of the ritual in building cultural identity between mountainous (Dani Tribe) in Manokwari and coastal (Doreri Tribe) communities in Manokwari, Papua. A qualitative method with a comparative case study approach was used to analyze the differences in practices, symbolic meanings, and contributions of the stone-burning tradition in shaping cultural identity in the two groups. Findings revealed significant variations in implementing and interpreting the ritual's meaning, reflecting adaptations to different natural and social environments. Even so, the value of tradition as a social glue and reinforcement of cultural identity is still maintained in both groups. This result strengthens the theory of cultural adaptation and demonstrates the flexibility of ritual practice in preserving its emblematic nature. This research contributes to a deeper understanding of local culture's dynamics and tradition's function in contemporary society. Practical implications include the development of cultural preservation and tourism strategies that are more responsive to regional diversity. Further research is recommended to expand the scope of the communities studied and conduct long-term studies to understand changes in traditional practices over time.